Investigating the Effect of Entrepreneurial Orientation of Jordanian Higher Education Institutions on Customer Orientation - Al-Rawadiah, Waleed Eid (Jordan Journal of Business Administration, 2022)
1 PhD, Public Relations Department Director, Mutah University, Jordan. Received on 24/7/2020 and Accepted for Publication on 7/10/2020. This study aims to determine the level of entrepreneurship orientation, customer orientation and the impact of entrepreneurship orientation on customer orientation of Jordanian public universities. For this study, entrepreneurial orientation dimensions used are: proactiveness, risk-taking and innovativeness. Jordanian public universities represent the sampling frame for this study, while academics working in leadership positions in these universities represent the unit of analysis (presidents, vice-presidents, deans, deputy deans and heads of academic departments). Three public universities were chosen using the judgmental sampling method based on the region (north, central and south) and the size of the university. These universities were Yarmouk University, the University of Jordan and Mutah University. A survey was conducted of all 341 academics working in leadership positions. 213 valid questionnaires were returned, representing a response rate of 63%. Using SPSS 26.0 and SmartPLS 2.0 software, data collected was analyzed by using the Partial Least Square (PLS) method. The results of the study indicate that proactiveness does not affect customer orientation, while risk-taking and innovation positively affect customer orientation